Seabird Concentrations in Late Summer Along the Coasts of Devon and Ellesmere Islands, N.W.T. - McLaren, Peter L.; Renaud, Wayne E. (ARCTIC, 1982)
The presence of large concentrations of northern fulmars and black-legged kittiwakes along coasts of Devon and Ellesmere islands was documented in 1976 and 1978 by aerial surveys. Fulmars were present along these coasts from late July until mid-September, with peaks in late August and early September along Devon Island, and mid-September along Ellesmere Island. Black-legged kittiwakes were abundant along Devon Island after mid-September, but common along Ellesmere Island from late August to late September. Densities of both species were significantly higher in front of glaciers than along coastlines.Key words: northern fulmar, black-legged kittiwake, arctic distribution, late summer, glacier front, Devon Island, Ellesmere Island